Optimalisasi Pengembangan Kurikulum: Sinergi Kearifan Lokal, AI, Ekologi, Neurosains dalam Meningkatkan Kualitas Pendidikan - Putri, Alya Juwita; Safitri, Riski Winda (Journal of Innovation in Teaching and Instructional Media, 2025)
The development of a learning curriculum that is relevant to the challenges and dynamics of the times requires a strong theoretical foundation so that it can be implemented optimally by policy makers and education practitioners. This study aims to optimize the development of a learning curriculum that is responsive to the challenges and goals of today's education. The method used is a literature study by critically analyzing various theoretical and empirical sources related to curriculum models. Through this analysis, the study identified key principles such as alignment of learning objectives and evidence-based evaluation. The novelty of this study lies in the curriculum development model that synergizes local wisdom, ecology, artificial intelligence (AI), and neuroscience in improving education. The contribution of this study is to provide a theoretical basis for policy makers and education practitioners in designing a curriculum that is more relevant to the challenges and goals of today's education.